Co-offending and bribery: the recruitment of participants to corrupt schemes and the implications for prevention. Issue 4 (October 2018) - Button, Mark; Shepherd, David; Blackbourn, Dean
Abstract This paper explores the rarely researched areas of co-offending and bribery. Based upon interviews with six persons convicted of bribery-related offences and other cases in the public domain, the paper explores how previously 'clean' persons are recruited to corrupt schemes. In doing so, the paper draws on Reason's resident pathogen theory on safety and uniquely applies it to bribery. The paper also identifies common recruitment techniques used by corruptors and proposes pathogen network analysis as a novel method for enhancing bribery prevention.